2016
DOI: 10.1590/1677-5449.004016
|View full text |Cite
|
Sign up to set email alerts
|

Absence of the celiac trunk and trifurcation of the common hepatic artery: a case report

Abstract: Anatomical variations of the celiac trunk and its branches are particularly important from a surgical perspective due to their relationships with surrounding structures. We report here a particularly rare variant involving absence of the celiac trunk in association with trifurcation of the common hepatic artery. These variations were found in an adult male cadaver. We perform a review of the literature and discuss the clinical and embryological significance of these variations. Recognition of celiac trunk and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 13 publications
1
6
0
1
Order By: Relevance
“…They observed that approximate 20% of patients had some type of hepatic artery variation [ 18 ]. Interestingly, Badagabettu et al [ 19 ] published a cadaver case report of common hepatic anatomy that shared similarities to our donor anatomy. Their patient had a common hepatic artery that trifurcated into the right hepatic artery, left hepatic artery, and the gastroduodenal artery.…”
Section: Discussionsupporting
confidence: 56%
“…They observed that approximate 20% of patients had some type of hepatic artery variation [ 18 ]. Interestingly, Badagabettu et al [ 19 ] published a cadaver case report of common hepatic anatomy that shared similarities to our donor anatomy. Their patient had a common hepatic artery that trifurcated into the right hepatic artery, left hepatic artery, and the gastroduodenal artery.…”
Section: Discussionsupporting
confidence: 56%
“…The absence of the celiac trunk was reported in five of the 12 studies of this review 4 , 9 , 18 , 19 , 26 . In these cases, the common gastric, splenic and hepatic arteries originated independently directly from the abdominal aorta (item d, Figure 2 ) 4 , 9 , 19 . During the developmental process, primitive arteries are longitudinally anastomosed formed and regress to some extent, where they remain throughout life.…”
Section: Discussionmentioning
confidence: 71%
“…In one case, the three branches emerged directly from the abdominal aorta. Badagabettu SN et al 4 Single Corpse dissection Absence of celiac trunk. Common hepatic artery, left gastric and splenic artery with independent origin in the aorta.…”
Section: Methodsmentioning
confidence: 99%
“…where the celiac trunk was absent and the arteries arose independently from the abdominal aorta [13]. Yadav et al reported a case of a female cadaver in 2014 [22] while another case of an adult male cadaver was reported by Badagabettu in 2016 [23].…”
Section: Discussionmentioning
confidence: 99%
“…However since the first report of Saint-Hillaire only 31 reported cases of such variation have been demonstrated by Iacob et al 2014 [25]. Since then 4 additional cases have been reported to the best of our knowledge [22][23][24]26]. The majority of these cases reported worldwide were observed during anatomical dissections in cadaveric studies, while others were detected by imaging studies.…”
Section: Discussionmentioning
confidence: 99%